2013
DOI: 10.1890/es13-00100.1
|View full text |Cite
|
Sign up to set email alerts
|

High predation on small populations: avian predation on imperiled salmonids

Abstract: Abstract. Generalist predators can contribute to extinction risk of imperiled prey populations even through incidental predation. Quantifying predation on small populations is important to manage their recovery, however predation is often challenging to observe directly. Recovery of prey tags at predator colonies can indirectly provide minimum estimates of predation, however overall predation rates often remain unquantifiable because an unknown proportion of tags are deposited off-colony. Here, we estimated ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 51 publications
2
55
1
Order By: Relevance
“…Our average tag recovery efficiency of 21% is slightly higher than several recent avian predation studies with similar direct-feeding study designs, all of which found that recovery of tags fed directly to birds was less than 10% (Osterback et al 2013;Scoppettone et al 2014;Teuscher et al 2015). Hostetter et al (2015) directly fed PIT-tagged hatchery trout to Caspian terns Hydroprogne caspia, doublecrested cormorants, and California gulls Larus californicus and found tag deposition rates on nearby colonies of 71, 51, and 15%, respectively, but most of their feeding trials were conducted on birds while they were on or immediately adjacent to the colonies, which likely elevated their tag deposition rates greatly.…”
Section: Water Body Yearcontrasting
confidence: 74%
See 2 more Smart Citations
“…Our average tag recovery efficiency of 21% is slightly higher than several recent avian predation studies with similar direct-feeding study designs, all of which found that recovery of tags fed directly to birds was less than 10% (Osterback et al 2013;Scoppettone et al 2014;Teuscher et al 2015). Hostetter et al (2015) directly fed PIT-tagged hatchery trout to Caspian terns Hydroprogne caspia, doublecrested cormorants, and California gulls Larus californicus and found tag deposition rates on nearby colonies of 71, 51, and 15%, respectively, but most of their feeding trials were conducted on birds while they were on or immediately adjacent to the colonies, which likely elevated their tag deposition rates greatly.…”
Section: Water Body Yearcontrasting
confidence: 74%
“…Declines in avian predation rates related to distance from colonies have been previously demonstrated (e.g., Fasola and Bogliani 1990;Osterback et al 2013) and would be expected for birds such as adult pelicans that rear chicks with high energy needs and that have high energy demands of their own. The highest observed pelican predation rates in this study were usually at waters within 100 km of the nearest colony except at CJ Strike Reservoir, which was over 200 km from the nearest colony yet still received relatively heavy predation pressure by pelicans in some years.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although previous work in Scott Creek identified or predicted characteristics such as size and origin that were associated with survival of juvenile salmonids Satterthwaite et al 2012;Sogard et al 2012) and documented high rates of western gull predation on these same populations (>30%; Osterback et al 2013), it was unknown whether gulls consumed individuals that would otherwise experience high survival rates. The results from this study provide the first empirical evidence that western gulls are consuming predominately wild steelhead, including many larger wild individuals that are critical to the persistence of the population.…”
Section: Figmentioning
confidence: 99%
“…Although populations may occasionally be able to rebound from temporary periods of elevated mortality (Germano & Joyner 1988, Zylstra et al 2013, increasing intensity, frequency, and duration of mortality events, coupled with habitat loss and fragmentation and a more physiologically stressful climate (Zylstra et al 2013, Lovich et al 2014 pose serious threats to the persistence of tortoise populations (Brook et al 2008). Furthermore, as tortoise populations continue to decline, stochastic predation events on small populations may have an increasingly important effect on tortoise persistence (Medica et al 2012, Osterback et al 2013. …”
Section: Discussionmentioning
confidence: 99%